Experience and perceived quality of care of patients and their attendants in a specialized mental hospital in Bangladesh - Nuri, Nazmun Nahar; Sarker, Malabika; Ahmed, Helal Uddin; Hossain, Md. Didar; Beiersmann, Claudia; Jahn, Albrecht (International journal of mental health systems, 2019)
A person’s perception of health service quality depends on his or her expectations and priorities. If the perception of care is good, then it eventually enhances future health service utilization, adherence to treatment and desired outcomes. Understanding a patient’s perspective is key for delivering a better quality patient-centred health care service. This study explored experience and perception of patients and their attendants of mental health care services at the National Institute of Mental Health (NIMH) which is the only national level mental health institute in Bangladesh. NIMH is located in the capital city and provides specialized mental health care services for the whole population.